Pengaruh Pertumbuhan Ekonomi terhadap Kualitas Lingkungan di 6 Negara Asean - Andre Putra; Melti Roza Adry (Universitas Negeri Padang, 2022)
This study examines the analysis of the effect of economic growth onenvironmental quality in 6 ASEAN countries. This research type is descriptiveand inductive research. The data used is panel data for 6 ASEAN countries fromthe period 2008 to the period 2019. Descriptive and inductive analysistechniques. The inductive analysis includes (1) a t-test and (2) F test with a 5%significance level. The analytical method used in this research is the RobustMethod of Panel Data Regression Analysis. The results of this study indicatethat (1) linear economic growth has a positive and insignificant effect onenvironmental quality, (2) non-linear economic growth has a negative andinsignificant effect on environmental quality, and (3) energy consumption has apositive and insignificant effect on environmental quality. environment, (4)transportation infrastructure has a positive and insignificant effect onenvironmental quality in 6 ASEAN countries.